A New High-Throughput-Screening-Assay for Photoantimicrobials Based on EUCAST Revealed Unknown Photoantimicrobials in Cortinariaceae - Fiala, Johannes; Schöbel, Harald; Vrabl, Pamela; Dietrich, Dorothea; Hammerle, Fabian; Artmann, Desirée Josefine; Stärz, Ronald; Peintner, Ursula; Siewert, Bianka (Frontiers in Microbiology, 2021)
Antimicrobial resistance is one of the biggest health and subsequent economic threat humanity faces. Next to massive global awareness campaigns, governments and NGOs alike stress the need for new innovative strategies to treat microbial infections. One of such innovative strategies is the photodynamic antimicrobial chemotherapy (PACT) in which the synergistic effects of photons and drugs are exploited. While many promising reports are available, PACT –and especially the drug-design part behind– is still in its infants. Common best-practice rules, such as the EUCAST or CLSI protocols for classic antibiotics as well as high-through-put screenings, are missing and this in turn hampers the identification of hit structures. Hit-like structures might come from synthetic approaches or from natural sources. They are identified via activity-guided synthesis or isolation strategies. As source for new antimicrobials, fungi are highly ranked. They share the same ecological niche with many other microbes and consequently established chemical strategies to combat with the others. Recently, in members of the Cortinariaceae, especially of the subgenus Dermocybe, photoactive metabolites were detected. To study their putative photoantimicrobial effect, a photoantimicrobial high-throughput screening (HTS) based on The European Committee on Antimicrobial Susceptibility Testing (EUCAST) was established. After validation, the established HTS was used to evaluate a sample-set containing six colorful representatives from the genus Cortinarius (i.e., Cortinarius callisteus, C. rufo-olivaceus, C. traganus, C. trivialis, C. venetus, and C. xanthophyllus). The assay is built on a uniform, LED-based light irradiation across a 96-well microtiter plate, which was achieved by a pioneering arrangement of the light emitting diodes. The validation of the assay was achieved with well-known photoactive drugs, so-called photosensitizers, utilizing six distinct emission wavelengths (exc = 428, 478, 523, 598, or 640 nm) and three microbial strains (Candida albicans, Staphylococcus aureus, and Escherichia coli). Evaluating the extracts of six Cortinarius species revealed two highly promising species, i.e., C. rufo-olivaceus and C. xanthophyllus. Extracts from the latter were photoactive against the gram-positive S. aureus (c = 7.5 µg/mL, H = 30 J/cm², λ = 478 nm) and the fungus C. albicans (c = 75 µg/mL, H = 30 J/cm², λ = 478 nm).